The incidence of VP shunt infection in a middle-income nation: a retrospective analysis of a pediatric population - Campbell, Dwayne; Sinclair, Shane; Cooke, Dwaine; Webster, Dwight; Reid, Marvin (Frontiers in Surgery, 2023)
Objective To investigate the incidence of infection after ventriculoperitoneal shunt (VPS) insertion at the Bustamante Hospital for Children (BHC), Jamaica, West Indies. Method Of the 178 patients managed by the Neurosurgery team at BHC, who underwent surgery between 2010 and 2016, 122 patients were subjected to the cerebrospinal fluid (CSF) diversion procedure through a VPS placement. The patients excluded from this study included those with a VPS placed at another institution or one placed prior to the study period. There is a notable transition that saw a switch from the use of the Codman uni-port to Medtronic shunts in 2014–2015, which initiated the process of reuse of shunt passers. Clinical data were retrospectively collected from operating theater logs and available manual health records. Results Over the 7-year study period of the 122 first-time shunt placements done, 17 patients (13.9%) had positive CSF cultures, with an additional six (4%) having CSF pleocytosis with negative cultures. The most common isolate was the Staphylococcus species, occurring in 60% of VPS infections. The median time to shunt infection was 2 months. Of the 72 Codman shunts placed, six became infected, and 21.7% (10 of 46) of the Medtronic shunts became infected. Conclusion The rate of incidence of VPS infection was 13.9% for the period between 2010 and 2016, with most infections occurring after 2014. The major causative agent was Staphylococcus species at 60% within a median 2 months of surgery. Overall, this compares well with data reported in the literature.